The impact of artificial intelligence technology in education on the learning habits of Chinese vocational college students - Zhang Rui (Journal of Exploration of Vocational Education, 2025)
ABSTRACT：With the gradual popularization of the application of AI technology in vocational colleges and universities, AI technology is changing students' learning methods and habits, which not only improves the personalized and interactive teaching, but also makes students' learning methods more flexible and diversified. However, in the process of widespread application of AI technology, how to balance the relationship between technology and teaching, how to ensure the fairness and sustainability of technology, is still a problem that educators need to think about and solve. These backgrounds provide theoretical basis and practical significance for this paper to study the influence of AI technology on the learning habits of Chinese vocational college students.This study will selects a vocational college located in Tangshan, Hebei Province, China through the method of case study to determine (1) What type of AI technology do the vocational college students in China prefer to use? (2) Why do vocational college students in education use AI? (3) How does AI technology impact the vocational college students' learning habits in China? The data will be collected through classroom observation and interview. Thematic analysis was used to process the data collected by the study.This study hopes to systematically analyze the specific impact of artificial intelligence tools on the learning habits of Chinese vocational college students, including the changes in students' learning behaviors and ways of thinking.The results of this study will help to better integrate vocational skills into the teaching environment of Chinese vocational schoolsThis is especially reflected in guiding the future of artificial intelligence technology to better integrate into China's vocational college education.